Development of a New Converging Thermal Wave Technique for Diffusivity Measurement of High Conductivity Thin Foils - Husin, Mohd Shahril (2008)
Major problems in measuring thermal diffusivity by using conventional optical technique arise due to difficulties in detecting the thermal signals particularly from high conductivity material in the form of thin foils. Despite the laser beam being tightly focused to form a heating ring on the sample surface, to the point that it could damage the sample, to induce converging thermal waves, the collected signals remain weak. The problems were overcome in this report by using a very large number of optical heating rings instead of a single heating ring in the conventional method. The thermal wave signals at the centre of the ring were generated subsequent to the absorption of the optical pulse beam in the form of a very large number of concentric rings. The signal was found to fit very reasonably well to the theoretical model signal based on very large number of concentric heating rings. The capability of the new design was proven from the measurement of thermal diffusivity of standard thin foils of Al, Cu, Zn, Ni and Brass of thickness in the range of ()0.75200 μm− with accuracy within 1%. In the case of Al and Cu foils, its thermal diffusivity was successfully measured for much thinner foil of thickness down to and as compare torespectively in the previous report.